The Implications of X-ray Use in Chuna Manual Therapy from the Viewpoint of Korean Medicine Doctors - Tae Gyu Kim; Yumi Gi; Kyu Jin Yang; Ki-Beom Lee; Hooin Jo; Jongho Choi; Yoon Jae Lee; Sanghun Lee; In-Hyuk Ha (MEDrang Inc., 2018)
Background The purpose of this survey study was to understand how utilization of X-rays as an adjunct to Chuna manual therapy (CT) supports treatment, as assessed by Korean medicine doctors (KMDs). Methods A survey was emailed to all 18,289 members of the Association of Korean Oriental Medicine (AKOM)to determine the implications of X-ray use in CT. Surveys were collected from September 22, 2017 to October 15, 2017. Results Of the 18,289 KMDs 562 completed the survey. The implications of a radiological diagnosis (X-ray) with CT was assessed using 5 items in a questionnaire: time to diagnosis, accuracy of treatment, patient comprehension and satisfaction, CT effect, and safety of CT. Survey participants identified improvement in patient comprehension and satisfaction as the most important factor for X-ray use with CT, followed by increased safety of CT. From the determinant factors for selection of CT intensity and specific techniques, severity of clinical symptoms was shown to be the most influential factor. Degenerative changes of the spine and degree of spinal malposition were also reported to be highly influential. Conclusions The KMDs' that participated in this study indicated that utilization of X-rays in conjunction with CT administration improved patient comprehension and satisfaction, and CT safety. Installation of radiological equipment in Korean medicine clinics where CT is provided may increase safety and patients' satisfaction.